The productivity of innovation in Portugal - Nuno Araújo; Leonardo Costa (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
In this research innovation is considered as a production process, with outputs and inputs. The purpose is to compare the productivity of innovation across the twenty seven Member States of the European Union (EU-27), with a particular focus on Portugal. The data on inputs and outputs of innovation were collected from the Innovation Union Scoreboard 2010 report and cover the EU-27 Member States, from 2006 to 2010. The Total Factor Productivity index (TFP index) was used as the technique for data analysis. The choice of this technique was mainly determined by its flexibility and by data constraints. Two types of TFP indexes were computed: i) TFPt (time), which compares the productivity of innovation in each Member State with its productivity in a base year; ii) TFPs (space), which compares the productivity of innovation in each Member State with the productivity of the EU-27 average. Results show larger TFPs differences across Member States than TFPt differences. Concerning TFPt, there is a reduction of productivity in most of the Member States during the time length, which can be explained by the recent world financial crisis. This was the case of Portugal, where average TFPt in the time length is slightly below 1. The seven Member States that did not lose any productivity are mostly from Eastern Europe, Member Sates which have entered the European Union and acceded to its structural funds more recently. Concerning TFPs, Portugal presents average TFPs well above 1. The Portuguese average TFPs value is close to the one of Germany and higher than the one of Sweden. The Innovation Union Scoreboard 2010 report classifies Portugal as Moderate innovator and Germany and Sweden as Innovation leaders. This research has found the marginal productivity of innovation in Portugal to be similar to the one of Germany and higher than the one of Sweden. Differences between Portugal, Germany, and Sweden, such as the ones reported in the Innovation Union Scoreboard 2010, can be explained by the fact of Portugal having fewer resources allocated to innovation than Germany and Sweden have. The TFPs results show in which Member States innovation investment pays the most.
Keywords: 650; EU-27; innovation; Portugal; production process; productivity; TFP index